Balancing Constitutional Rights and Personal Data Protection for Citizens in the Digital Society: A Proportionality Test Analysis of Constitutional Court Decisions - Charity, May Lim; Anshory, Syaifuddin (Department of Sociology, Universitas Nasional (Indonesia), 2026)
The development of digital technology and the enactment of the Personal Data Protection Law (PDP Law) have raised constitutional tensions between the right to privacy and freedom of expression, particularly when the disclosure of personal data is related to public interest. This conflict raises questions about how the Constitutional Court balances these two rights in Decision Number 135/PUU-XXIII/2025 and the extent to which the approach used reflects the proportionality test. This study aims to analyse the practice of balancing rights in the decision, examine its compliance with the stages of the proportionality test, and formulate a more systematic model for applying proportionality in the context of digital constitutionalism. The study employs normative legal methods with conceptual, legislative, and case study approaches, as well as limited comparative analysis. The research results indicate that the Court has substantively carried out constitutional balancing, but has not yet operationalized the proportionality test explicitly and systematically, especially in terms of necessity and proportionality in the strict sense. The implication is that formalization of the proportionality test is needed in adjudication and legislative practices to maintain the balance of rights in a rational, consistent, and democratic manner in the era of digital governance.